2015
DOI: 10.1038/onc.2015.324
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variations of HLA-I and activation of NKp30 pathway determine the sensitivity of gastric cancer cells to the cytotoxicity of natural killer cells

Abstract: Nude mice are important in vivo model for characterization of cell malignancy behavior; however, many cancer cells fail to form tumors in it. Understanding this defective mechanism may provide novel insights into tumorigenesis and how tumor cells escape innate immunity. Whole-genome sequencing was conducted on two gastric cancer (GC) cells, BGC823 and AGS, which do and do not form tumors in nude mice, to identify their genomic differences relevant to natural killer (NK) cells. We found that the tumorigenic cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These results correspond to those of previous studies in other cancers 14 , 19 , 29 , 30 .At the same time, in vivo assay using MKN45 and SGC7901 cells also verified the inhibitory and stimulative role of Enah on cell proliferation and metastasis. Here, we did not perform this assay using the AGS cell because in 2016, R Xing 31 and colleagues confirmed that the GC cell line AGS, which expresses low level of HLA-I upon activation of the NKp30/MAPK/interleukin (IL)-12 or IL-2 pathway, was susceptible to NK cell-mediated lysis, leading to the failure of AGS cells to form tumors in nude mice. Altogether, our data demonstrate that Enah plays an important role in GC pathogenesis by the promotion of cell proliferation and metastesis and the inhibition of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results correspond to those of previous studies in other cancers 14 , 19 , 29 , 30 .At the same time, in vivo assay using MKN45 and SGC7901 cells also verified the inhibitory and stimulative role of Enah on cell proliferation and metastasis. Here, we did not perform this assay using the AGS cell because in 2016, R Xing 31 and colleagues confirmed that the GC cell line AGS, which expresses low level of HLA-I upon activation of the NKp30/MAPK/interleukin (IL)-12 or IL-2 pathway, was susceptible to NK cell-mediated lysis, leading to the failure of AGS cells to form tumors in nude mice. Altogether, our data demonstrate that Enah plays an important role in GC pathogenesis by the promotion of cell proliferation and metastesis and the inhibition of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several common immune checkpoints (CD274, CTLA-4, LAG3, PD-CD1, ATIC) were identified to be highly expressed in low-risk populations for better clinical application of ICI. HLA acts as an antigen presenting factor regulating immune response in gastric cancer [ 40 ]. Lower risk group had higher expression of HLA-related genes, indicating a more active local immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Although NK cells in the resting state have little cytotoxicity against GC, NK cells induced by the K562-mb15-41BBL cell line in vitro have strong effects on GC cytotoxicity and strong antitumor activity in animal experiments ( 45 ). Decreased human leukocyte antigen class I (HLA-I) expression leads to decreased NK cell infiltration in GC and is insensitive to NK cell activity ( 46 ). Death-associated protein kinase 1 (DAPK1) downregulates the IKKβ/CSN5 axis in GC, inhibits PD-L1 expression, and activates the killing ability of NK cells ( 47 ).…”
Section: The Constitution Of Gc Tmementioning
confidence: 99%